CFD Analysis of the Eccentricity Ratio on Journal Bearing due to Differences in Lubrication Type - Vivi Failawati; Mohamad Yamin; Sri Poernomosari; Amar Ratnakar Naik (The Indonesian Institute of Science and Technology Research, 2022)
Lubrication on journal bearings plays a vital role in reducing metal-to-metal friction, separates the reliable components. Often there is a decrease in lubrication conditions, which will cause failure or a change in roughness to the inner surface. Direct metal-to-metal contact between the bearing's inner and journal surface will gradually deform the bearing. In diesel engine applications, lubrication is aiming to minimize failure or damage to the journal bearing. This paper investigates a 3D CAD model of a journal bearing using the ANSYS Computational Fluid Dynamics software. The effect of eccentricity ratio is analyzed for semisynthetic lubricating oil R3 10W-30 and synthetic oil. The result shows that synthetic oil has a considerable pressure compared to R3 10W-30, especially at a higher eccentricity ratio.